Investigation of alumina additive in lubricant oil for enhanced engine performance - Bagavathi, Krishnan (2012)
Nanoparticles have been studied as additives to lubrication oils for reducing friction and wear. The purpose of this paper is to investigate the effect of different size nanoparticles on engine oil. Nanolubricant containing 13 nm and 52 nm Al2O3 nanoparticles in engine oil as base fluid in different concentrations, 0.5-2.5% vol. produced from two step method and the thermal conductivity, flash point, pour point and pH were examined. Experimental results show that the thermal conductivity of 13 nm and 52 nm Al2O3 nanolubricant are enhanced as much as 9.52% and 5.55% respectively. Thermal conductivity increases with increased volume concentration and temperature. There is an increase in thermal conductivity when the size of the particle decreases. Improvement up to 14.73% and 11.05% seen in the flash point of the lubricant with 13 nm and 52 nm Al2O3 nanoparticles respectively. Among the two nanooils, lubricant added with 13 nm Al2O3 has the best pour point recorded and the increment is 100%. The pour point temperature increases on the negative side as concentration increases. The pH showed a good dispersion of nanoparticles and it was proved to have the dispersion maintained for long period, which was attributed to the higher charge on the surface of nanoparticles. The test results are useful for the application of nanoparticle additive for engine oil.